2015
DOI: 10.1021/acsnano.5b00271
|View full text |Cite
|
Sign up to set email alerts
|

Better Catalysts through Microscopy: Mesoscale M1/M2 Intergrowth in Molybdenum–Vanadium Based Complex Oxide Catalysts for Propane Ammoxidation

Abstract: In recent decades, catalysis research has transformed from the predominantly empirical field to one where it is possible to control the catalytic properties via characterization and modification of the atomic-scale active centers. Many phenomena in catalysis, such as synergistic effect, however, transcend the atomic scale and also require the knowledge and control of the mesoscale structure of the specimen to harness. In this paper, we use our discovery of atomic-scale epitaxial interfaces in molybdenum-vanadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…One additional factor to be considered is that the time of experiments by some researchers may not be long enough to observe significant changes. Even the presence of the M2 phase affecting selectivity in propane ammoxidation is not agreed upon [15,50,52]. The roles of active exposed planes during the reaction are also debated [77,80].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One additional factor to be considered is that the time of experiments by some researchers may not be long enough to observe significant changes. Even the presence of the M2 phase affecting selectivity in propane ammoxidation is not agreed upon [15,50,52]. The roles of active exposed planes during the reaction are also debated [77,80].…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of M2 phase in the catalytic system is found to improve acrylonitrile selectivity [15,50], although a recent study by Woo et al suggested the M1 phase is the only phase required for both the activity and selectivity in propane ammoxidation [52]. The STEM microscopy approach has been adopted to analyze the synergetic effects of this M1/M2 mixture [15,51].…”
Section: Propane Ammoxidation To Acrylonitrilementioning
confidence: 99%
“…Therefore, NMF provides a natural representation of components that is consistent with physical constraints, which makes it an excellent phase mapping method. As an example, in the case of a Mo‐V‐Te‐Ta oxide catalyst, M1 and M2 phases coexist with a clear boundary visible in the STEM image. A stack of FFT spectra is collected by sliding a window of a fixed size across the STEM image of the oxide catalyst (Figure F).…”
Section: Structure Representation Via Dimension Reductionmentioning
confidence: 99%
“…Very recently, He et al. revealed epitaxial M1/M2 intergrowth, which are both catalytically active . However, knowledge of how the complex oxide behaves under unavoidable electron‐beam irradiation during electron microscopy characterization is still lacking.…”
Section: Figurementioning
confidence: 99%
“…The phase‐pure M1 catalyst was synthesized by using a hydrothermal method . The chemical composition of the M1 phase is listed as (65.6±0.5) at % molybdenum, (16.5±0.6) at % vanadium, (6.7±0.3) at % tellurium, and (11.3±0.4) at % niobium .…”
Section: Figurementioning
confidence: 99%